The Value of a Statistical Life in Sweden Estimates from Two Studies using the "Certainty Approach" Calibration - Mikael Svensson (Örebro University School of Business, 2007)
Stated preference methods using surveys to elicit willingness to pay have been shown to suffer from hypothetical bias and scope/scale bias. Hypothetical bias usually means that willingness to pay is exaggerated in the hypothetical scenario and scope/scale bias means that there is an insensitivity in willingness to pay with regard to the amount of goods or the size of a good being valued. Experimental results in social psychology and economics have shown that only trusting the most certain respondents can potentially solve the problem with hypothetical bias and scope/scale bias. This paper presents the results of two different surveys in Sweden estimating the willingness to pay to reduce traffic mortality risks by only including the most certain respondents. Using the full sample, estimates of VOSL are 4.2 and 7.3 million. Estimates of VOSL on the subset of the samples only including the most certain respondents are lower and consistent between the two surveys with values of 2.9 and 3.1 million.
Keywords: D80; I18; Q51; 330; Value of a Statistical Life; Contingent Valuation; Hypothetical Bias; Calibration; Certainty Approach